Developing polyphenolic acetates as radiation countermeasure agents: current status and future perspectives. Issue 4 (April 2020) - Venkateswaran, Kavya; Shrivastava, Anju; Prasad, Ashok K.; Parmar, Virinder S.; Dwarakanath, Bilikere S.
Highlights: Acute radiation syndrome (ARS); protein acetylation in cellular radiation response. Semi-synthetic polyphenolic acetates (PAs) and modification of radiation response. We provide an insight into PAs as potential radiation countermeasure agents. PAs as mitigators of ARS; considerations in designing countermeasure agents. PAs as adjuvant in radiotherapy of tumors for protection of normal cells. Abstract : Total-body exposure to ionizing radiation (TBI) results in life-threatening acute radiation syndrome (ARS), which encompasses hematopoietic and gastrointestinal (GI) injuries and results in dose-dependent morbidity and mortality. Management of ARS warrants the deployment of effective medical countermeasure agents (MCM) that protect against and/or mitigate lethal radiation injury. The polyphenolic acetate (PA) 7, 8-diacetoxy-4-methylthiocoumarin (DAMTC) has been identified as a potential MCM against ARS by virtue of it mitigating the lethal effects of TBI in C57BL/6 mice. Herein, we describe current evidence, including mechanistic aspects, for the use of PAs as MCMs against ARS and provide perspectives for their further development as approved drugs for the mitigation of ARS.